2007
DOI: 10.1099/mic.0.2006/005694-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of OmpX, an Ail homologue of Yersinia pestis KIM

Abstract: The goal of this study was to characterize the Yersinia pestis KIM OmpX protein. Yersinia spp. provide a model for studying several virulence processes including attachment to, and internalization by, host cells. For Yersinia enterocolitica and Yersinia pseudotuberculosis, Ail, YadA and Inv, have been implicated in these processes. In Y. pestis, YadA and Inv are inactivated. Genomic analysis of two Y. pestis strains revealed four loci with sequence homology to Ail. One of these genes, designated y1324 in the Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(171 citation statements)
references
References 59 publications
5
159
2
2
Order By: Relevance
“…Recently, the Y. pestis Ail protein was also shown to mediate cell binding, cell invasion, bacterial autoaggregation, and serum resistance (3,28). This finding was somewhat surprising, since Y. pestis Ail is nearly identical to Yersinia pseudotuberculosis Ail, which has been reported to confer serum resistance but not play a role in adhesion or invasion of tissue culture cells (67).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Recently, the Y. pestis Ail protein was also shown to mediate cell binding, cell invasion, bacterial autoaggregation, and serum resistance (3,28). This finding was somewhat surprising, since Y. pestis Ail is nearly identical to Yersinia pseudotuberculosis Ail, which has been reported to confer serum resistance but not play a role in adhesion or invasion of tissue culture cells (67).…”
mentioning
confidence: 52%
“…Genomic sequencing of three of these mutants identified the locus of the mariner insertion as the ail gene of Y. pestis (20). Ail has been defined previously in pathogenic Yersinia species as mediating cell attachment and invasion as well as serum resistance (3,28,40,67). Homologues of Ail in other genera have also been referred to as an opacity factor, since deletion of the locus results in an altered colony morphology phenotype (7).…”
Section: Resultsmentioning
confidence: 99%
“…However, as the molecular mechanisms of these proteins become characterized, it is apparent that conserved functions can be assigned to several members of this family. Rck, PagC (Salmonella choleraesuis), and Ail were shown to mediate serum resistance (3-5, 23, 24), whereas adhesion and/or invasion properties have been observed in all of the aforementioned proteins, with the exception of Y. pseudotuberculosis Ail (25)(26)(27)(28)(29). Furthermore, functional fH and C4BP binding have now been described in Rck (21,30) and Y. enterocolitica and Y. pseudotuberculosis Ail (10,11,15).…”
Section: Discussionmentioning
confidence: 99%
“…85 However, Kim and colleagues further demonstrated that another outer membrane protein, OmpX, also plays a major role in invasion of Caco-2 epithelial cells 85 and has been shown to be necessary for the invasion of Hep-2 cells by Yersinia pestis and C. sakazakii. 86,87 As a consequence, it was observed that ompA/X deletion mutants were significantly less efficient in the dissemination of the bacterium to other organs such as the liver and spleen in vivo.…”
Section: Crossing the Gut Barrier-invasionmentioning
confidence: 99%